Dietary diversity and associated factors among infants and young children in three West African countries - Janmohamed, Amynah; Baker, Melissa M.; Doledec, David; Ndiaye, Fatou; Konan, Ahmenan Claude Liliane; Leonce, Amoakon; Kouadio, Koffi Landry; Beye, Maguette; Yattara, Mohamed L.; Dissieka, Romance (Frontiers in Public Health, 2024)
Providing children healthy diversified diets is important for their optimal growth and development. The high prevalence of under-nourishment during the critical early life period is of serious concern in West Africa. We assessed the level of dietary diversity and associated factors for children aged 6-23 months in Côte d'Ivoire, Niger and Senegal. Prior 24 h dietary intake was assessed for 3,528 children (Côte d'Ivoire: N=118; Niger: N=763; Senegal: N=2,647) using the Diet Quality Questionnaire survey tool administered to primary caregivers. Cluster random sampling was conducted for urban and rural areas in Niger and Senegal and simple random sampling was used in Côte d'Ivoire, where only rural households were selected. Survey data were analyzed to determine children's intake of items from eight food groups: breast milk; grains, roots, tubers and plantains; pulses, nuts and seeds; dairy products; flesh foods; eggs; vitamin A-rich fruits and vegetables; and other fruits and vegetables. Minimum Dietary Diversity (MDD) was assessed based on the consumption of ≥ 5 of the 8 food groups. In all countries, the majority of children were ≥ 12 months of age and from rural households. Children from poor/very poor households ranged from 32.4% to 41.9%. MDD prevalence was 54.2% in Côte d'Ivoire, 33.3% in Niger and 30.8% in Senegal. In all three countries, children 12-23 months had significantly higher consumption of six of the food groups, compared to those 6-11 months, and children ≥ 12 months had a higher likelihood of MDD, compared to infants, in Niger (aOR=4.25; 95% CI: 2.46, 7.36) and Senegal (aOR=2.69; 95% CI: 2.15, 3.35). MDD prevalence was higher among children in urban, compared to rural, areas in Niger (p=0.020) and Senegal (p<0.001) and significantly higher in the wealthiest, compared to poorest, households. This study suggests most young children in Côte d'Ivoire, Niger and Senegal are not receiving an adequately diversified diet, with a reliance on starchy staples and lower intake of high-quality protein sources. Our results highlight socio-economic barriers to attaining dietary diversity in these settings and stress the urgent and continuing need for investments in strategies that support optimal complementary feeding practices.